The defense of Puračić and the beginnings of the Hadžiefendić legion - Hamzić, Omer; Šaković, Edin (Historical Thought, 2025)
After several unsuccessful attempts of the NDH military forces to, with the help of the Germans, neutralize with the uprising affected areas of eastern Bosnia, the insurrectional wave at Majevica and Ozren in late 1941 gains in its intensity, potentially endangering the very city of Tuzla. In early November 1941, after burning and expulsion of the Bosniak population from Devetak and Milino Selo, the rebels from Ozren were very close to Puračić. At the last moment and with extreme effort the danger was removed by Muhamed-aga Hadžiefendić, with his Home Guard unit from Tuzla (III. Battalion of the 8th Home Guard Regiment). During these battles he realized the immense danger threatening Bosniaks, not only in Puračić, but also in the wider area of Tuzla, and it was exactly in Puračić that he made the decision to form a special military unit, made up of Bosniaks, which would be able to defend these territories – the famous Hadžiefendić legion, as it was its popular name. Leaving aside the broader elaboration of causes and effects of its creation, the activity during the war and the disappearance of this formation, the aim of this paper is to, by showing the military-political situation around Puračić at end of 1941, remind on bringing decision regarding its formation, which is linked to Puračić, to show its, from the very beginning, territorial and defensive character, its first defensive positions and successful military action against insurgents around Puračić.